Tryptophan metabolism, its relation to inflammation and stress markers and association with psychological and cognitive functioning: Tasmanian Chronic Kidney Disease pilot study. Issue 1 (December 2016) - Karu, Naama; McKercher, Charlotte; Nichols, David; Davies, Noel; Shellie, Robert; Hilder, Emily; Jose, Matthew
Abstract Background Adults with chronic kidney disease (CKD) exhibit alterations in tryptophan metabolism, mainly via the kynurenine pathway, due to higher enzymatic activity induced mainly by inflammation. Indoles produced by gut-microflora are another group of tryptophan metabolites related to inflammation and conditions accompanying CKD. Disruptions in tryptophan metabolism have been associated with various neurological and psychological disorders. A high proportion of CKD patients self-report symptoms of depression and/or anxiety and decline in cognitive functioning. This pilot study examines tryptophan metabolism in CKD and explores associations with psychological and cognitive functioning. Methods Twenty-seven adults with CKD were part of 49 patients recruited to participate in a prospective pilot study, initially with an eGFR of 15–29 mL/min/1.73 m2 . Only participants with viable blood samples and complete psychological/cognitive data at a 2-year follow-up were included in the reported cross-sectional study. Serum samples were analysed by Liquid Chromatography coupled to Mass Spectrometry, for tryptophan, ten of its metabolites, the inflammation marker neopterin and the hypothalamic–pituitary–adrenal (HPA) axis marker cortisol. Results The tryptophan breakdown index (kynurenine / tryptophan) correlated with neopterin (PearsonR  = 0.51P  = 0.006) but not with cortisol. Neopterin levels also correlated with indoxyl sulfate (R  = 0.68, P  < 0.0001) and 5 metabolites of tryptophan (R range 0.5–0.7, allP  ≤ 0.01), which were all negatively related to eGFR (P  < 0.05). Higher levels of kynurenic acid were associated with lower cognitive functioning (SpearmanR  = −0.39, P  < 0.05), while indole-3 acetic acid (IAA) was correlated with anxiety and depression (R  = 0.52 andP  = 0.005, R  = 0.39 andP  < 0.05, respectively). Conclusions The results of this preliminary study suggest the involvement of inflammation in tryptophan breakdown via the kynurenine pathway, yet without sparing tryptophan metabolism through the 5-HT (serotonin) pathway in CKD patients. The multiple moderate associations between indole-3 acetic acid and psychological measures were a novel finding. The presented pilot data necessitate further exploration of these associations within a large prospective cohort to assess the broader significance of these findings.